2019
DOI: 10.25134/erjee.v7i2.1773
|View full text |Cite
|
Sign up to set email alerts
|

Native English Speakers Versus Non-Native English Speakers: The Impact of Language Teachers on Efl Learner's English Proficiency

Abstract: In the field of TESOL, the perception that Native English Speaking Teachers (NESTs) are better than Non-Native English Speaking Teachers (NNESTs) has influenced language schools, recruitment policies and institutional leadership practices. The tendency to recruit more NESTs and achieve improved learning outcomes can be seen in English as a Foreign Language (EFL) and English as a Second Language (ESL) contexts. This paper aims to investigate whether NESTs or NNESTs have any impact on the EFL learners� language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
0
21
1
Order By: Relevance
“…Thus recently, many scholars, especially in Asian countries, have tried hard to investigate the notion of being NEST and NNEST in ELT. Elyas & Alghofaili (2019) observed two groups of students taught by NEST and NNEST at Saudi Arabian University. Their findings indicated that teacher's native-ness and backgrounds have no significant effects on Saudi EFL learners speaking and listening skills.…”
Section: Nest and Nnest Dichotomymentioning
confidence: 99%
“…Thus recently, many scholars, especially in Asian countries, have tried hard to investigate the notion of being NEST and NNEST in ELT. Elyas & Alghofaili (2019) observed two groups of students taught by NEST and NNEST at Saudi Arabian University. Their findings indicated that teacher's native-ness and backgrounds have no significant effects on Saudi EFL learners speaking and listening skills.…”
Section: Nest and Nnest Dichotomymentioning
confidence: 99%
“…Others would simply settle on using a variation of English that are unique to that region (Pradana, 2019). The position of native English teachers are challenged, as non-native teachers can teach with the same efficiency (Elyas & Alghofaili, 2019).…”
Section: Pradana and Enamentioning
confidence: 99%
“…A research by Crystal mentions that both native and nonnative teachers have their own advantages and drawbacks, and that both variations have merit (As cited in Pradana, 2019). Other researchers adapt a more critical stance to the debate, mentioning the indifference between native and non-native English speaking teachers in their participants (Elyas & Alghofaili, 2019) or the fact that their participants are showing signs of accepting ELF (Wang, 2016).…”
Section: Pradana and Enamentioning
confidence: 99%
“…Thus, students seem to esteem other aspects other than the teachers' native language. Another study by Alghofaili and Elyas (2019) investigated the impact of NESTs and NNESTs on the Saudi EFL learners' achievements in listening and speaking skills. The results revealed that the nativeness of teachers does not influence the speaking and listening skills of Saudi EFL students.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Also, Ürkmez (2015) found that 96% of the 120 Turkish students prefer NESTs over NNESTs for teaching speaking skills. However, most English learners regard fluency as the most essential skill (Alghofaili, Elyas, 2019). Considering that, the noticeable preference for NESTs at teaching speaking in many contexts is understandable.…”
Section: Learners' Motivation and Preference Of Nests And Speakingmentioning
confidence: 99%